1966
DOI: 10.1115/1.3670951
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Study of the Dynamics of an Elastic Linkage

Abstract: The transverse vibrational characteristics of the connecting rod in a slider-crank mechanism are investigated. The equations of motion are derived, simplified, and solved. For the solution, two different numerical techniques are employed and correlation is achieved. Two dimensionless parameters, S the speed parameter and Z the physical parameter, arise during the derivation of the equations of motion. These parameters can be used by the designer as an indication of the vibrational activity of the mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1970
1970
1993
1993

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…For some time analysts have considered the effects of both link elasticity [1][2][3][4][5][6][7][8] 1 and connection clearances [8][9][10][11][12] on the dynamic behavior of planar mechanisms. Researchers have found that elasticity in the links of mechanisms has a substantial effect on the dynamic behavior of the mechanisms, while the results of the clearance studies have shown that the introduction of clearances in mechanisms causes substantial increases in the connection forces, resulting in degradation of the performance and life of the system.…”
Section: Introductionmentioning
confidence: 99%
“…For some time analysts have considered the effects of both link elasticity [1][2][3][4][5][6][7][8] 1 and connection clearances [8][9][10][11][12] on the dynamic behavior of planar mechanisms. Researchers have found that elasticity in the links of mechanisms has a substantial effect on the dynamic behavior of the mechanisms, while the results of the clearance studies have shown that the introduction of clearances in mechanisms causes substantial increases in the connection forces, resulting in degradation of the performance and life of the system.…”
Section: Introductionmentioning
confidence: 99%
“…where e0/represents the j-th order term in the expansion of e 0 which is defined in equation (9). Applying the same procedure to the equations of motion (25)- (27), the following sequence of equations is obtained:…”
Section: Application Of the Methods Of Multiple Scales (Mms)mentioning
confidence: 99%
“…Order e- 9 2 /~ = (e%)x = 0, (50) and (51), it is seen that b I = b 2 = 0. Hence, u~(x, To, Ta, T2) must be zero.…”
Section: Application Of the Methods Of Multiple Scales (Mms)mentioning
confidence: 99%
See 2 more Smart Citations